2009
DOI: 10.1063/1.3270159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of proton migration and dissociation in core-excited ethyne probed by multiple ion momentum imaging

Abstract: The study focuses on the rapid geometry change in ethyne excited near the carbon 1s edge. Core excitation and ionization lead to population of dicationic states in ethyne. We study three competing dissociation pathways associated with deprotonation in the linear ethyne molecule, and two cases of rapid proton migration. We investigate the alignment of the molecule in the excited state and find startling differences in these three cases. We present evidence for a strong anisotropy in the production of H2+/C2+ fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…A fragmentation channel indicating a dibridged configuration was identified in acetylene. 35 This channel was isolated by filtering on H + 2 /C + 2 coincidences and it was found that we monitor only molecules undergoing a cis-bending motion. The sharp alignment that was registered for acetylene in the C 1s…”
Section: A Transient Isomerizationmentioning
confidence: 99%
“…A fragmentation channel indicating a dibridged configuration was identified in acetylene. 35 This channel was isolated by filtering on H + 2 /C + 2 coincidences and it was found that we monitor only molecules undergoing a cis-bending motion. The sharp alignment that was registered for acetylene in the C 1s…”
Section: A Transient Isomerizationmentioning
confidence: 99%
“…Isomerization of acetylene (HCCH) to form vinylidene (H 2 CC) has been studied in the neutral molecule, as well as singly and doubly charged acetylene ions 1,2,[24][25][26][27][28][29][30][31][32][33][34][35][36] . Acetylene cations are important not only as a model for molecular dynamics and radiation damage investigations, but also in a range of applications, from plasma devices 37 , combustion 38 , semiconductor manufacturing 39 and to understanding planetary atmospheres 40 .…”
mentioning
confidence: 99%
“…Acetylene cations are important not only as a model for molecular dynamics and radiation damage investigations, but also in a range of applications, from plasma devices 37 , combustion 38 , semiconductor manufacturing 39 and to understanding planetary atmospheres 40 . Isomerization of the dication has been investigated in synchrotron experiments 1,2,27,28,34 . Osipov et al 1,2 performed ion-ionphotoelectron and ion-ion-Auger electron coincidence measurements to study the fragmentation of the dication formed on core ionization of acetylene.…”
mentioning
confidence: 99%
“…5 and related to reaction (7). It is well known this reaction is very fast [42][43][44] and occurs more quickly than the usual rotation period of the precursor dication, which is on the order of picoseconds. The results indicate rota distribution, and therefore t an upper limit to the intrins propensity to occur with th zation vector.…”
Section: Double Photoionization Of Acetylenementioning
confidence: 98%